“The library is so much more than books”: considerations for the design and implementation of teen digital mental health services in public libraries - Knapp, Ashley A.; Hersch, Emily; Wijaya, Clarisa; Herrera, Miguel A.; Kruzan, Kaylee P.; Carroll, Allison J.; Lee, Sydney; Baker, Alex; Gray, Alanna; Harris, Vann; Simmons, Robert; Kour Sodhi, Deepika; et al. (Frontiers in Digital Health, 2023)
Background: Adolescence is a vulnerable developmental period, characterized by high rates of mental health concerns, yet few adolescents receive treatment. Public libraries support adolescents by providing them with access to teen programming, technological resources, and have recently been providing mental health services. Digital mental health (DMH) services may help libraries provide scalable mental health solutions for their adolescent patrons and could be well positioned to address the mental health needs of historically underrepresented racial and ethnic (HURE) adolescents; however, little research has been conducted on the compatibility of DMH services with adolescent patron mental health needs or resource needs of library workers supporting them. Methods: The research team formed a partnership with a public library, which serves a large HURE adolescent population. We conducted needs assessment and implementation readiness interviews with 17 library workers, including leadership, librarians, and workers with specialized areas of practice. Interview questions focused on library infrastructure, as well as library needs and preferences around the design and implementation of DMH services for adolescents. We used the Consolidated Framework for Implementation Research as guiding implementation determinant framework to code and analyze the interview transcripts. Results: Our findings revealed library workers play an important role in guiding patrons to desired resources and share a goal of implementing adolescent DMH resources into the library and elevating marginalized adolescents’ voices. Existing library resources, such as the library’s role as a safe space for adolescents in the community, close relationships with external and community organizations, and availability of no-cost technological resources, could help facilitate the implementation of DMH services. Barriers related to community buy-in, mental health stigma, and library worker confidence in supporting adolescent mental health could affect service implementation. Conclusions: Our findings suggest public libraries are highly promising settings to deploy DMH services for adolescents. We identified important determinants that may impact the implementation of DMH services in public library settings. Special considerations are needed to design services to meet the mental health needs of HURE adolescent populations and those adolescents’ most experiencing health inequities.